Secado de maderas tropicales en estufas convencionales - Zavala Zavala, David (Instituto de Ecología, A.C., 2016)
Some of the drying problems of tropical species in conventional kilns are associated with the diversity of their technological properties, with the difficulty of gathering adequate volumes of the same species to apply them a drying schedule according to the wood characteristics, and with the high cost of the process that determines the profitable capacity of the kilns and limits its utilization to dry small volumes of lumber. An alternative to overcome these limitations is  to  integrate  groups of similar species in volumes according to the capacity of the kilns, to be able to apply them the same drying schedule. This study was performed with the goal of integrating groups of tropical wood species that could be dried with the same schedule in order to make feasible the drying process in conventional kilns. For this study, the sawn lumber of 33 tropical species was used, which was integrated in two groups according to their specific gravity, 16 species with specific gravity of 0.30 to 0.60, and 17 with 0.60 to 0.90. A drying schedule was formulated for each group, that was evaluated in a conventional kiln, analyzing the deffects of each board  before and after the drying process (checks, twist, cup, bow and crook). In general, the two schedules applied to the two groups of species were adequate since no significant defects  due to the drying process were observed. In the group of species with specific gravity below 0.60, 10 of them  dried faster than the other 6, which suggest the possibility of subgrouping them to optimize the used of the dry kilns applying them a faster schedule. With the schedule for the species with specific gravity higher than 0.60, 7 of them dried at aproximately half of the time (10 - 14 days) than the other 10, which suggests the possibility of subgrouping them to optimize the use of dry kilns. If it is not possible to regroup the species within each category  to achieve a uniform process, it is suggested to integrate the lumber with similar moisture content and dimensions in each one of the two groups analized in this study.